1991
DOI: 10.1007/bf00335851
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the biology of Eisenia fetida and Eisenia andrei (Oligochaeta)

Abstract: In these two articles J.M. Venter was mistakenly credited only with research assistance, whereas in fact he was a co-author. In each case his name should have appeared in second position: A. J. Reinecke, J. M. Venter, and S. A. Vilj oen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…Dominguez et al () experimentally evidenced that there is reproductive isolation between E. fetida and E. andrei connected with postcopula isolation mechanisms; the two species mate and produce cocoons, although these cocoons did not hatch. Similar results were obtained by Reinecke and Viljoen (). In contrast, Andre () showed that interspecific mating between E. fetida and E. andrei produced hybrid worms which were sterile and had an intermediate pigmentation pattern.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dominguez et al () experimentally evidenced that there is reproductive isolation between E. fetida and E. andrei connected with postcopula isolation mechanisms; the two species mate and produce cocoons, although these cocoons did not hatch. Similar results were obtained by Reinecke and Viljoen (). In contrast, Andre () showed that interspecific mating between E. fetida and E. andrei produced hybrid worms which were sterile and had an intermediate pigmentation pattern.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Andre () showed that interspecific mating between E. fetida and E. andrei produced hybrid worms which were sterile and had an intermediate pigmentation pattern. Sheppard () obtained fertile offspring of interspecific mating resembling the parental types, and he referred this phenomenon “facilitated self‐fertilization.” Mixed populations and the resulting hybridization could hamper reproduction rates if maximum yield is to be attained (Reinecke and Viljoen, ). Presumably, the effects of hybridization in mixed populations may be dependent on the previous life history of syntopic species, thus further studies applying modern research techniques may be very fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…corethrurus has a relatively long life cycle (1 year; Hamoui, 1991;Buch et al, 2011) and low fecundity (17-118 cocoons individual −1 and only one hatchling cocoon −1 ; Pineda and Hernández, 1983;Bhattacharjee and Chaudhuri, 2002) compared with E. andrei, that completes its life cycle in 45-51 days and produces >700 cocoons individual −1 and on average 2-3 hatchlings cocoon −1 (Domínguez et al, 2005;Reinecke and Viljoen, 1991). These characteristics mean that mass-rearing, although possible is more time-consuming (Pashanasi, 2007) and will yield only with great effort the quantities necessary for routine ecotoxicological tests.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies, often reaching conflicting findings, were subsequently undertaken to shed more light on the recognition of two forms (e.g. André 1963;Avel 1929;Jaenike 1982;Reinecke and Viljoen 1991). Most recently, genetic evidence confirmed the presence of two distinct species (Perez-Losada et al 2005).…”
mentioning
confidence: 99%